1990
DOI: 10.1007/bf01580025
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of shock waves

Abstract: Summary.Extracorporeal shock wave lithotripsy has become established worldwide as the method of choice for the treatment of nephrolithiasis and ureterolithiasis over the last 10 years. Although initial studies showed no damaging effects of the shock waves on organs and tissues, numerous recent reports have presented evidence for severe acute effects and chronic complications after shock wave treatment. The pathophysiological effects on kidneys and the histopathological effects on organs or tissues in man and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 50 publications
0
24
0
3
Order By: Relevance
“…37 The physical mechanisms related to the cavitation phenomenon that cause both stone destruction and tissue damage are very complex, not well understood and hardly experimentally controllable. 35,[37][38][39] The fact that ESWL can cause tissue damage, inspired experiments that applied lithotripter induced shockwaves to tumors in vivo. While several first studies in animal models did not show any impact of shock waves on tumor growth, 36 some results seemed encouraging, for example a delayed tumor growth in mice 40 and even complete remission of dorsal skin tumors in hamsters.…”
Section: Shock Waves Produced By Lithotriptersmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The physical mechanisms related to the cavitation phenomenon that cause both stone destruction and tissue damage are very complex, not well understood and hardly experimentally controllable. 35,[37][38][39] The fact that ESWL can cause tissue damage, inspired experiments that applied lithotripter induced shockwaves to tumors in vivo. While several first studies in animal models did not show any impact of shock waves on tumor growth, 36 some results seemed encouraging, for example a delayed tumor growth in mice 40 and even complete remission of dorsal skin tumors in hamsters.…”
Section: Shock Waves Produced By Lithotriptersmentioning
confidence: 99%
“…Most striking for a possible shock wave based tumor therapy was a study on different normal and malignant cell lines, which showed no selective effect. 38 When the energy deposited by the lithotripter is reduced below the lethal value, it is possible to permeabilize the cells without killing them. [42][43][44][45][46] In this way, molecules present in the surrounding medium can diffuse into the cells.…”
Section: Shock Waves Produced By Lithotriptersmentioning
confidence: 99%
“…In some cases, as SW-induced cavitation fields deviate far from the intended treatment region, undesired damage might be caused in bone and/or surrounding tissues because of unforeseen acoustic energy deposition. 17,24 Therefore, the strain energy distribution should be taken seriously in SW treatments.…”
Section: Fem Simulations Of Strain Energy Distributions In the Bonmentioning
confidence: 99%
“…17 Therefore, better physical understandings of SW propagation characteristics and energy deposition during ESWT processes may be a prerequisite for standardizing treatment dosage, optimizing future protocols, and even providing guidance to manufacturers regarding machine designs.…”
Section: -8979/2013/113(24)/244901/7mentioning
confidence: 99%
“…It has been hypothesized that cavitation near the application site may have been the cause. 6 The peak pressure amplitude of radial shockwave generators used for extracorporeal shockwave therapy (ESWT, lithotripsy) is approximately 20 times higher than the output of chiropractic instruments. 3 In addition, ESWT generally requires between 1,000 and 4,000 impulses per treatment while the Activator devices are limited to just one impulse per treatment site.…”
mentioning
confidence: 99%